UPAYA MENINGKATKAN PEMBELAJARAN SENAM IRAMA MELALUI METODE BAGIAN PADA SISWA KELAS V SD NEGERI 02 PADURAKSA KECAMATAN PEMALANG KABUPATEN PEMALANG TAHUN AJARAN 2012/ 2013 (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2013)
This study aims to determine the effectiveness of dealing with the matter of shape formation stages 1 to 4 or 1 to 8 to improve learning outcomes rhythmic gymnastics at the fifth grade students of SD Negeri 02 Paduraksa of Pemalang Regency academic year 2012/2013.Data collection techniques used observation and tests.The results show that student achievement is not yet complete on the existing prasiklus 9 students or 30.00%, in the first cycle decreased to 6 students or 20.00% and the second cycle students decreased to 2 or 6.67%. Student achievement that have been completed on prasiklus there are 21 students or 70.00% in the first cycle increased to 24 students or 80.00% and the second cycle to 28 students or 93.33%.Conclusion This study shows that through the method can improve the ability of part rhythmic gymnastics, the fifth grade students of SD Negeri 02 Paduraksa of Pemalang Regency academic year 2012/2013.